2014
DOI: 10.1007/s11060-014-1633-9
|View full text |Cite
|
Sign up to set email alerts
|

Pentavalent technetium-99m-dimercaptosuccinic acid [Tc-99m (V) DMSA] brain SPECT: does it have a place in predicting survival in patients with glioblastoma multiforme?

Abstract: Pentavalent technetium-99m dimercaptosuccinic acid (Tc-99m (V) DMSA) is reported as a useful tool for detection of residual or recurrent gliomas. We aimed to investigate the prognostic value of Tc-99m (V) DMSA brain SPECT in patients with glioblastoma multiforme (GBM). 40 patients [21 males and 19 females; mean age 48.6 ± 12.2 years] with GBM were included. Tc-99m (V) DMSA brain SPECT was done after surgery and before onset of radiation therapy or chemotherapy (Baseline study), at 4-6 weeks and at 6 months as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…Patients with positive 99m Tc-DM-SA-V visual findings or higher L/NL ratio at the early or delayed phases had shorter OS compared with the negative cases or those with lower L/NL ratios. Amin et al [34] assessed the prognostic role of 99m Tc-DMSA-V in 40 patients with GBM and concluded that higher degrees of tracer uptake were associated with worse survival that concurs with our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with positive 99m Tc-DM-SA-V visual findings or higher L/NL ratio at the early or delayed phases had shorter OS compared with the negative cases or those with lower L/NL ratios. Amin et al [34] assessed the prognostic role of 99m Tc-DMSA-V in 40 patients with GBM and concluded that higher degrees of tracer uptake were associated with worse survival that concurs with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Amin et al . [34] assessed the prognostic role of 99m Tc-DMSA-V in 40 patients with GBM and concluded that higher degrees of tracer uptake were associated with worse survival that concurs with our results.…”
Section: Discussionsupporting
confidence: 85%